1999
DOI: 10.1063/1.123054
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of fullerene films

Abstract: Microwave dielectric properties of tunable capacitors employing bismuth zinc niobate thin films

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Relevant to these results are prior studies indicating that solid C 60 arrays rotate almost freely in a rotationally disordered high‐temperature, face‐centered cubic phase (above 260 K at atmospheric pressure). This motion is said to slow down and is transformed into a ratcheting or rocking motion in an orientation‐ordered simple cubic phase at low temperatures and high pressures . Su et al demonstrated a structural phase transition at 260 K as well as an anomaly at 90 K resulting from a glass transition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevant to these results are prior studies indicating that solid C 60 arrays rotate almost freely in a rotationally disordered high‐temperature, face‐centered cubic phase (above 260 K at atmospheric pressure). This motion is said to slow down and is transformed into a ratcheting or rocking motion in an orientation‐ordered simple cubic phase at low temperatures and high pressures . Su et al demonstrated a structural phase transition at 260 K as well as an anomaly at 90 K resulting from a glass transition.…”
Section: Resultsmentioning
confidence: 99%
“…This motion is said to slow down and is transformed into a ratcheting or rocking motion in an orientation-ordered simple cubic phase at low temperatures and high pressures. [38][39][40] Su et al 38,39 demonstrated a structural phase transition at 260 K as well as an anomaly at 90 K resulting from a glass transition. Furthermore, these investigators observed a Debye-like relaxation in the dielectric response, e 0 and tan d versus f curves at three temperatures for C 60 (OH) 29 and Sc 3 N@C 80 (OH) 18 are provided in Figures 3 and 4, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…8,9 Su et al 10 observed Debye-like relaxation peaks and extracted an activation energy of 277 meV. However, from the temperature-dependant complex permittivity of C 60 ͑111͒ epitaxial films Fartash 11 detected signs of the order-disorder transition, but none for any glass transition in the ranges of temperature and frequency of his measurements.…”
mentioning
confidence: 93%
“…Nevertheless, the chemical process may be more complex since several -bonds of fullerenes may participate in the surface reactions simultaneously, depending on the adsorption sites and the electron delocalization. Fullerene-based precursors may be potentially useful to serve as low-k materials 39 or surface passivation agents upon deposition on semiconductor surfaces due to their unique structural and electronic characteristics. The main advantage of fullerenes lies in their high volumes with ample space within the spheres, their low polarizability and excellent thermal stability.…”
Section: Introductionmentioning
confidence: 99%